Evaluating Phase Constituents, Magnetic Properties and Microstructure of Nickel Ferrite Nanoparticles Synthesized by Sol-Gel Auto-Combustion - S. Alamolhoda (Journal of Advanced Materials in Engineering, 2017)
In this research, nickel ferrite nanoparticles were synthesized by sol-gel auto-combustion route, and the effect of calcination temperature on phase constituents, magnetic properties and microstructure of the synthesized nanoparticles was evaluated using X-ray Diffraction (XRD), Vibrating Sample Magnetometer (VSM) and Scanning Electron Microscopy (SEM). XRD results were submitted to quantitative analysis. Microstructural studies and crystallite size calculations showed formation of nanoparticles. XRD results showed that the combustion product consisted of NiFe2O4, α-Fe2O3, NiO, and FeNi3 phases. FeNi3 was eliminated by calcination, and the amounts of NiO and α-Fe2O3 were modvlated by changing in calcination temperature. Saturation magnetization changed from 37emu/g in combustion product to 30emu/g by calcination at 600°C, due to decomposition of FeNi3 magnetic phase and formation of higher amount of antiferromagnetic hematite phase. Also, the coercivity values increased, that could be due to increasing the amount of nickel ferrite phase and eliminating FeNi3 phase. Saturation magnetization reached to 43emu/g in calcinated sample at 1000°C due to the reaction between hematite and NiO phases that led to formation of higher amount of nickel ferrite to 43emu/g. Coercivity value dropped out to 127Oe by calcination at 1000°C, the reason of which could be incresing of particle size and formation of multi domain magnetic particles.